2010
DOI: 10.2217/nnm.10.41
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Nanofeatures, In Vitro Thrombus Lysis Activity and In Vivo Thrombolytic Activity of Poly-α,β-Aspartyl- L -Alanine

Abstract: Upon entering the stomach, intestinal tract, blood and tissue fluids, poly-alpha,beta-DL-aspartyl-L-alanine assembled to small nanoparticles or nanoblocks to escape the entrapment by macrophages and exhibited desirable thrombolytic action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Also, the fibrin plate assay is a simple screening method where fibrinolytic activity is related to the diameter of the lysis zone on a fibrin plate produced by the investigated nanomaterial. Ex vivo or in vitro thrombolytic assays are usually based on gravimetric methods comparing weight of the thrombus after treatment with tested and control nanomaterials . Thrombolytic or fibrinolytic activity of nanomaterials observed by a simple screening assay should be further investigated to elucidate whether the tested article exhibits direct fibrinolytic activity or activates plasminogen, or activates plasminogen activators.…”
Section: Methods For Evaluation Of the In Vitro Effects Of Nanomaterimentioning
confidence: 99%
“…Also, the fibrin plate assay is a simple screening method where fibrinolytic activity is related to the diameter of the lysis zone on a fibrin plate produced by the investigated nanomaterial. Ex vivo or in vitro thrombolytic assays are usually based on gravimetric methods comparing weight of the thrombus after treatment with tested and control nanomaterials . Thrombolytic or fibrinolytic activity of nanomaterials observed by a simple screening assay should be further investigated to elucidate whether the tested article exhibits direct fibrinolytic activity or activates plasminogen, or activates plasminogen activators.…”
Section: Methods For Evaluation Of the In Vitro Effects Of Nanomaterimentioning
confidence: 99%
“…Showing the relationships between the bioactivities of small molecules with their TEM images, between the concentrations of small molecules with their TEM images, and between the structures of small molecules with their TEM images has been our interests. 33 36 To elucidate the contribution of the nanoproperty to the advantages of three conjugates, this study systematically characterizes their nanofeatures. The Faraday–Tyndall effect, size distribution, and ζ-potential of three conjugates in water ensure their properties as a true solution and their use as nanomedicine ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…[64] The result found that this polymer assembled to various nanospecies exhibited concentration-dependent lysis action in vitro and dose-dependent thrombolytic action in vivo by escaping the entrapment of macrophages. [64] Although previous studies demonstrated the effect of accelerating thrombolysis using plasminogen activators (PAs) encapsulated liposomes or PEG microparticles by pressure-driven permeation, it was necessary to design new types of nanoparticles to enhance the therapeutic efficacy. Chung et al reported a new concept of accelerating thrombolysis with chitosan-coated plasminogen activators encapsulated in PLGA nanoparticles.…”
Section: Polymersmentioning
confidence: 96%
“…Lin et al reported poly‐α,β‐DL‐aspartyl‐L‐alanine from the thermal polycondensation of DL‐aspartic acid and the amidation of polysuccimide with L‐alanine as nanoscale assembly to the design of a thrombolytic agent. [ 64 ] The result found that this polymer assembled to various nanospecies exhibited concentration‐dependent lysis action in vitro and dose‐dependent thrombolytic action in vivo by escaping the entrapment of macrophages. [ 64 ] Although previous studies demonstrated the effect of accelerating thrombolysis using plasminogen activators (PAs) encapsulated liposomes or PEG microparticles by pressure‐driven permeation, it was necessary to design new types of nanoparticles to enhance the therapeutic efficacy.…”
Section: Therapymentioning
confidence: 99%
See 1 more Smart Citation